Immigrant entrepreneurs in rural England – An examination of the socio- cultural barriers facing migrant small businesses in Lincolnshire. (November 2020) - Hack-Polay, Dieu; Tenna Ogbaburu, Justice; Rahman, Mahfuzur; Mahmoud, Ali B
A growing body of literature recognises the crucial role played by immigrant entrepreneurs. However, certain socio-cultural barriers adversely affect their businesses in rural areas. Thus, this article examines the socio-cultural barriers facing immigrant entrepreneurs in Lincolnshire. Eleven semi-structured interviews were held with businesses owned by immigrants from diverse ethnic backgrounds. The findings identified migrant ethnocentrism, stereotypes, cultural differences and language differences as key socio-cultural barriers adversely affecting immigrant businesses in Lincolnshire. The research found that immigrant enterprises experienced growth issues, not just owing to the size of the market but also due to issues of embeddedness in the socio-economic nomenclature. The study found mixed embeddedness to be key to immigrant entrepreneurial success. This involves immigrant adaptation to develop relational embeddedness with the hosts, involvement with its social, structural and institutional frameworks. The study contributes to our understanding of the role of social, relational, structural and institutional embeddedness in steering fertile approaches to immigrant entrepreneurship in rural England which has been under-researched.